Thyroid Hormone Activation Regulates the Crosstalk between Breast Cancer and Mesenchymal Stem Cells - Annarita Nappi; Vittoria D’Esposito; Caterina Miro; Alessia Parascandolo; Annunziata Gaetana Cicatiello; Serena Sagliocchi; Lucia Acampora; Sepehr Torabinejad; Federica Restolfer; Maddalena Raia; Melania Murolo; Emery Di Cicco; et al. (Frontiers in Bioscience-Landmark)
Background: Thyroid Hormones (THs) critically impact human cancer. Although endowed with both tumor-promoting and inhibiting effects in different cancer types, excess of THs has been linked to enhanced tumor growth and progression. Breast cancer depends on the interaction between bulk tumor cells and the surrounding microenvironment in which mesenchymal stem cells (MSCs) exert powerful pro-tumorigenic activities. Methods: Primary human MSCs from healthy female donors were co-cultured with DIO2 knock out (D2KO) and wild type (WT) MCF7 breast cancer cells to assess cell growth, migration, invasion and the expression of known epithelial-mesenchymal transition (EMT)- and inflammation-related markers. Furthermore, a surgery-free intraductal delivery model, i.e., the Mouse-INtraDuctal (MIND) injection method, was used as a tool for in vivo characterization of breast tumor formation and progression. Results: In this study, we uncovered a novel role of THs in regulating the tumor-stroma crosstalk. MCF7 cells enhanced the intracellular activation of THs through the TH-activating enzyme, D2, fostering their EMT properties and the dialogue with MSCs. D2 inactivation reduced the invasiveness of MCF7 cells and their responsiveness to the pro-tumorigenic induction via MSCs, both in vivo and in vitro. Conclusions: Thus, we argue that intracellular activation of THs via D2 is a critical requirement for invasive and metastatic conversion of breast cancer cells, advising the blocking of D2 as a potential therapeutic tool for cancer therapy.